2013
DOI: 10.5688/ajpe77230
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Learning and Satisfaction With High-Fidelity Simulation to Teach Drug-Induced Dyspepsia

Abstract: Objective. To assess second-year pharmacy students' acquisition of pharmacotherapy knowledge and clinical competence from participation in a high-fidelity simulation, and to determine the impact on the simulation experience of implementing feedback from previous students. Design. A high-fidelity simulation was used to present a patient case scenario of drug-induced dyspepsia with gastrointestinal bleeding. The simulation was revised based on feedback from a previous class of students to include a smaller group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
0
29
1
Order By: Relevance
“…19 The introduction of human patient simulation into the curricula of pharmacy colleges and schools has occurred more recently, and several reports have described its benefits to student learning. [20][21][22][23][24][25][26] Only a few reports have examined the use of human patient simulation in an IPE experience among pharmacy students and those from other health disciplines. One report described the use of human patient simulation to teach patient safety, collaboration, and communication among an interprofessional group of students.…”
Section: Introductionmentioning
confidence: 99%
“…19 The introduction of human patient simulation into the curricula of pharmacy colleges and schools has occurred more recently, and several reports have described its benefits to student learning. [20][21][22][23][24][25][26] Only a few reports have examined the use of human patient simulation in an IPE experience among pharmacy students and those from other health disciplines. One report described the use of human patient simulation to teach patient safety, collaboration, and communication among an interprofessional group of students.…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of this evidence includes the use of highfidelity mannequin simulation instruction. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A number of outcomes (eg, self-perceived clinical skills, teamwork and interprofessional teamwork skills, blood pressure assessment) have been assessed using high-fidelity mannequins. Although it has been shown that high-fidelity mannequin simulation can increase knowledge retention in pharmacy education, data is lacking on retention of advanced cardiac life support (ACLS) knowledge and skills following simulation training.…”
Section: Introductionmentioning
confidence: 99%
“…While student SLM workshop attendance was mandatory, the participation in research activities was not, and, in addition to the positive comments, students' high survey response rates also illustrate the level of student enthusiasm and engagement in the SLMs. Previously, reports indicate that students appreciate communication simulation activities in the classroom, 32 even when used as an isolated teaching activity. 33 The four facilitators reflected on the strengths of SLMs immediately after their completion.…”
Section: Discussionmentioning
confidence: 99%